The influence of adult urine lead exposure on bone mineral densit: NHANES 2015-2018 - Wang, Shaokang; Zhao, Xiaofeng; Zhou, Runtian; Jin, Yuanzhang; Wang, Xiaonan; Ma, Xiaotian; Lu, Xiangdong (Frontiers in Endocrinology, 2024)
Introduction:Previous studies have indicated that exposure to heavy metals related to bone health is primarily limited to some common harmful metals, and the impact of lead has not been fully understood. This study aims to explore the relationship between urine lead exposure and bone density. Methods ： 1,310 adults were included from the NHANES database (2015-2018), and through generalized linear regression analysis and constrained cubic spline models, the association between lead levels and total bone density as well as lumbar spine bone density was explored. The study also examined the impact of combined exposure to lead and cadmium on bone density. Results and Conclusions: Urinary lead levels were significantly negatively correlated with total bone mineral density (β: -0.015; 95%CI: -0.024, -0.007) and lumbar spine bone mineral density (β: -0.019; 95%CI: -0.031, -0.006). Compared to the lowest three quartiles of lead levels, the adjusted odds ratios for T3 changes in total bone mineral density and lumbar spine bone mineral density were 0.974 (95%CI: 0.959, 0.990) and 0.967 (95%CI: 0.943, 0.991), indicating a significant negative trend. Further analysis with constrained cubic spline models revealed a nonlinear decreasing relationship between urinary lead and total bone mineral density as well as lumbar spine bone mineral density. Stratified analyses suggested that the relationship between urinary lead levels and bone mineral density might be significantly influenced by age, while gender showed no significant impact on the relationship. Moreover, combined exposure to lead and cadmium was found to be associated with decreased bone mineral density, emphasizing the potential synergistic effects between lead and cadmium on bone health. However, the specific mechanisms of lead and its effects on different populations require further comprehensive research. This study provides valuable insights for further exploration and development of relevant public health policies.